2008
DOI: 10.1002/jor.20833
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of articular and auricular cartilage as a cell source for the autologous chondrocyte implantation

Abstract: Articular (medial femoral condyle) and auricular cartilage (anithelix) was compared as a cell source for the autologous joint repair. Cells isolated from five human cadaveric donors were cultured parallel in the monolayer cultures and in the 3D alginate hydrogel constructs for 1 week. Cell morphology was controlled by the fluorescent microscopy and gene expressions of type I collagen (COL1), type II collagen (COL2), aggrecan (AGR), versican (VER), and elastin (ELS) were analyzed by the real-time polymerase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…The results of the present study indicated a higher expression profile of cartilage specific matrix components such as type II collagen in 2D and 3D articular chondrocyte cultures harvested from two species: human and swine and were therefore in accordance with data reported by Isogai et al (28), and Malicev et al (30), but did mostly not agree with the results of Chung et al (31).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The results of the present study indicated a higher expression profile of cartilage specific matrix components such as type II collagen in 2D and 3D articular chondrocyte cultures harvested from two species: human and swine and were therefore in accordance with data reported by Isogai et al (28), and Malicev et al (30), but did mostly not agree with the results of Chung et al (31).…”
Section: Discussionsupporting
confidence: 78%
“…In some cases, different individuals were used for the isolation of heterotopic chondrocytes and therefore inter-donor variance could not be excluded. Most importantly, chondrocytes of different monolayer passages were investigated, so that a divergent velocity of dedifferentiation which depends on the cartilage source (articular and auricular) could cause the differing results [dedifferentiation is enhanced in the more rapidly proliferating auricular chondrocytes compared with slowly proliferating articular chondrocytes (30)]. Therefore, we decided to study chondrocytes harvested from swine and to compare some of these results with those from similar experiments with human chondrocyte populations to exclude results that seem to be influenced by the donor species itself.…”
Section: Discussionmentioning
confidence: 99%
“…To date, we and others have evaluated the use of chondrocytes and mesenchymal stem cells (MSCs) from several anatomical locations for their applicability in cartilage regenerative medicine (Afizah et al, 2007;Asawa et al, 2009;Chung et al, 2008;Hellingman et al, 2011;Henderson et al, 2007;Isogai et al, 2006;Johnson et al, 2004;Kafienah et al, 2002;Karlsson et al, 2007;Kusuhara et al, 2009;Lohan et al, 2011;Malicev et al, 2009;Naumann et al, 2004;Panossian et al, 2001;Sakaguchi et al, 2005;Seda Tigli et al, 2009;Tay et al, 2004;van Osch et al, 2004;Vinardell et al, 2012;Xu et al, 2004;Yoshimura et al, 2007;Zhang and Spector, 2009). However, these studies often used non-expanded cells isolated from animals.…”
Section: Discussionmentioning
confidence: 99%
“…2002; Karlsson et al, 2007;Kusuhara et al, 2009;Lohan et al, 2011;Malicev et al, 2009;Naumann et al, 2004;Panossian et al, 2001;Sakaguchi et al, 2005;Seda Tigli et al, 2009;Tay et al, 2004;van Osch et al, 2004;Vinardell et al, 2012;Xu et al, 2004;Yoshimura et al, 2007;Zhang and Spector, 2009). However, precise comparison of the performance of culture-expanded human cells is lacking.…”
Section: The In Vitro and In Vivo Capacity Of Culture-expanded Human mentioning
confidence: 99%
“…In contrast, Kusuhara et al could observe elastic Wbers in bovine auricular, but not in articular, nasoseptal or costal chondrocytes constructs after 10 or 40 days in the nude mice (Kusuhara et al 2009). At gene expression level, elastin could be demonstrated in diverse culture systems of auricular chondrocytes and to a lesser degree also in articular chondrocytes (Malicev et al 2009;Kuhne et al 2010). On the other side, the full synthesis of elastic Wbers, which consist of elastin and microWbrils, might require more time and the time requirement might be species-dependent.…”
Section: Discussionmentioning
confidence: 81%